Epidemiology and Etiology of Mental Retardation - McDermott, Suzanne (Handbook of Intellectual and Developmental Disabilities, 2007)
Mental retardation (MR) is a manifestation of a heterogeneous set of impairments and conditions that result in cognitive limitation. It is a condition of medical, educational, and social importance. Physicians identify profound, severe, and moderate MR but rarely diagnose mild MR unless it is associated with a genetic or medical syndrome. From a medical perspective, the quest for etiology and the possibility of medical or surgical intervention to minimize deterioration are paramount. Educators, on the other hand are less concerned with causation than with academic achievement and school success. The majority of cases of mild MR is identified in school settings. Finally, the public uses the label to describe poor adaptive skills. Adults with MR who hold jobs, live independently, and participate in society are not always described as having MR. Thus some individuals characterized in childhood or adolescence as having mild MR become indistinguishable from the general population in adulthood.